Charlie Bone and the time twister - Nimmo, Jenny (Egmont UK Limited, 2010)
Back at Bloor's Academy after Christmas vacation, Charlie finds himself confronted with a new problem when young Henry Yewbeam, who vanished during a game of marbles in 1916, suddenly appears and needs help to find his family.